DEVELOPMENT OF A NEW SMART SURVEILLANCE SYSTEM FOR MONITORING SPORTS INJURIES. Issue 4 (1st February 2017) - Sadeghi, Mohsen; Alizadeh, Mohammad Hossein
Abstract : Background: There are several methods for monitoring sports injuries including simple questionnaires, text messaging and sophisticated surveillance systems. However, some problems related to inconsistency of injury definitions and classifications, high costs, data entry mistakes and lack of online technology usage may limit the efficacy of these methods and reduce validity of the recorded information. Objective: To develop a new smart surveillance system for recording, reporting and analysing sports injuries. Design: Common systems and methods for monitoring sports injuries were explored in the literature for identifying the potential problems and defects. Then, we searched for valid definitions and categories of sports injuries such as those available in consensus statements. Considering the popularity of smartphone amongst health care professionals, development of a connection between a special application and a computer software or another app was identified as the best way for designing a new surveillance system. Setting: Mobile app and computer software. Interventions (or Assessment of Risk Factors): A mobile app was designed on an android platform for determining the characteristics of players, injuries and exposures. Another app and a computer software were also developed for data receiving unit of the system that was able to save information and to send data to the client's application. Main Outcome Measurements: The data extracted from the smart surveillance system. Results: The first version of the smart system that utilized recommendations of the consensus statement on football injuries had capability of recording injuries in an effective manner and sending them to the server software in which the data could be classified and analysed. Conclusions: The new surveillance system for sports injuries is a technology-based system that links the medical staff of sports teams to organizations or researchers and speeds up recording and reporting the data of injuries.